Inuit-Centred Learning in the Inuit Bachelor of Education Program - Moore, Sylvia; Allen, Cheryl; Andersen, Marina; Boase, Doris; Campbell, Jenni-Rose; Doherty, Tracey; Edmunds, Alanna; Edmunds, Felicia; Flowers, Julie; Lyall, Jodi; Mitsuk, Cathy; Nochasak, Roxanne; et al. (Études Inuit Studies, 2016)
The Inuit Bachelor of Education (IBED) program in Labrador is a partnership between the Nunatsiavut Government (NG) and Memorial University of Newfoundland. It is preparing teachers to be key participants in NG’s education system. The IBED students and Sylvia Moore, the lead faculty member in the program, have based this paper on a collaborative presentation. The writers explore the tensions between the current provincial curriculum offered in the regional schools and a curriculum that is founded on Inuit history, culture, and worldview, restores the central role of the Inuit language, and is community-based as recommended in the 2011 National Strategy on Inuit Education. The students discuss four key threads of culturally relevant education: land, language, resources, and local knowledge. Moore reflects on how the IBED program incorporates these same elements to support Inuit identity and the developing pedagogy of the pre-service teachers.